2020
DOI: 10.3390/jcm9092898
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Neutrophil-to-Lymphocyte Ratio as a Prognostic Factor in Uterine Sarcoma

Abstract: Background: Recent studies have demonstrated that the tumor microenvironment, known to be influenced by inflammatory cells, plays a crucial role in cancer progression and clinical outcome of patients. The objective of the present study was to investigate prognostic values of preoperative neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) for disease-free survival (DFS) and overall survival (OS) of uterine sarcoma patients. Methods: Ninety-nine patients with uterine sarcoma treated in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…29 On the other hand, lymphocytes are involved in cell-mediated response to tumor infiltration, and a low lymphocyte count might result in inadequate immune response, and thus, be associated with unfavorable outcomes. 11 In the present study, lymphocyte counts were similar in LMS and LM, but WBC and neutrophil counts were higher in LMS patients (Tables 1 and 3), which is in accord with previous studies that reported an elevated neutrophil count was associated with a preoperative diagnosis of LMS. 4,18,30 The cutoffs of WBC and ANC in this study are in the normal range.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…29 On the other hand, lymphocytes are involved in cell-mediated response to tumor infiltration, and a low lymphocyte count might result in inadequate immune response, and thus, be associated with unfavorable outcomes. 11 In the present study, lymphocyte counts were similar in LMS and LM, but WBC and neutrophil counts were higher in LMS patients (Tables 1 and 3), which is in accord with previous studies that reported an elevated neutrophil count was associated with a preoperative diagnosis of LMS. 4,18,30 The cutoffs of WBC and ANC in this study are in the normal range.…”
Section: Discussionsupporting
confidence: 92%
“…32,34 Regarding gynecologic malignancies, high NLR is associated with poor clinical outcomes in ovarian, endometrial, and cervical cancer, and in uterine sarcoma. 11,32,33,35 In a metaanalysis conducted by Wu et al in cervical cancer, an elevated NLR was found to be closely associated with poor clinical outcomes and unfavorable clinicopathological factors. 36 Similarly, Jeong et al reported that an elevated preoperative NLR (≥2.60) was associated with poor clinical outcomes in uterine sarcoma patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is consistent with our findings. Furthermore, positive SP142 assay was found to be a more significant independent prognostic factor than the NLR, which has been reported as a prognostic factor in patients with various types of cancer (32,33). Interestingly, the survival subgroup analysis of ES patients indicating that positive results of each PD-L1 assay showed more distinct differences than with the analysis of LS patients.…”
Section: Discussionmentioning
confidence: 79%